Transcriptome Analyses of β-Thalassemia −28(A>G) Mutation Using Isogenic Cell Models Generated by CRISPR/Cas9 and Asymmetric Single-Stranded Oligodeoxynucleotides (assODNs) - Li, Jing; Zhou, Ziheng; Sun, Hai-Xi; Ouyang, Wenjie; Dong, Guoyi; Liu, Tianbin; Ge, Lei; Zhang, Xiuqing; Liu, Chao; Gu, Ying (Frontiers in Genetics, 2020)
β-thalassemia, caused by mutations in the human hemoglobin (HBB) gene, is one of the most common genetic diseases in the world. HBB −28 (A>G) mutation is one of the five most common mutations in China patients with β-thalassemia. However, few studies have been conducted to understand how this mutation affects the expression of pathogenesis related genes including globin genes due to limited homozygote clinical materials. Therefore, we developed an efficient technique using CRISPR/Cas9 combined with asymmetric single-stranded oligodeoxynucleotides (assODNs) to generate a K562 cell model with HBB -28(A>G) named as K562-28(A>G). Then, we systematically analyzed the differences between K562-28 (A>G) and K562 at the transcriptome level by high-throughput RNA-seq before and after erythroid differentiation. We found that HBB -28(A>G) mutation not only disturbed the transcription of HBB but also decreased the expression of HBG, which may further aggravate the thalassemia phenotype and partially explain the severer clinical outcome of β-thalassemia patients with HBB -28(A>G) mutation. Moreover, we found that K562-28(A>G) cell line is more sensitive to hypoxia and showed a defective erythrogenic program compared with K562 before differentiation. Importantly, all above mentioned abnormalities in K562-28(A>G) were reversed after correction of this mutation with CRISPR/Cas9 and assODNs, confirming the specificity of these phenotypes. Overall, this is the first time to analyze the effects of the HBB -28(A>G) mutation at whole-transcriptome level based on isogenic cell lines, providing a landscape for further investigation of the mechanism of β-thalassemia with HBB -28(A>G) mutation.